Analysis of Indonesian Coffee Exports to the United States of America on 1996-2021 Period - Adelia Megautami; Yuni Prihadi Utomo (IECON: International Economics and Business Conference, 2023)
Coffee is one of the largest international trade commodities in the world. This raises competitiveness and challenges for coffee producing countries in the world to produce good quality products, one of which is Indonesia. The Indonesian plantation sectoris an important sector for the national economy, producing superior coffee commodities inthe international market. This study aims to determine the effect Gross Domestic Product real United States, US dollar exchange rate, international coffee prices, Indonesian coffeeproduction, American coffee consumption, and world coffee production on the volume ofIndonesian coffee exports to the United States for the period 1996 to 2021 using regressionanalysis Ordinary Least Square (OLS). The results show that Indonesian coffee production has a positive effect and world coffee production has a negative effect on the volume of Indonesian coffee exports to the United States.Gross Domestic Product US real terms, USdollar exchange rate, international coffee prices, and US coffee consumption have no effecton the volume of Indonesian coffee exports to the US. Indonesian coffee exports to the United States, although still prospective, face quite tight competition in the international market.